The Concept of Wasathiyah in QS. 2:143 Analysis of the Ma'na Cum Maghza Approach - Khairuddin, K; Rahman, R; Perdamaian, P; Suardi, S; Wasalmi, W; Srg, Syahruddin (Universitas Muhammadiyah Surakarta, 2025)
Wasathiyah Islam has become one of the issues that has been widely researched recently. This issue arises as a response to the increasing behavior of extremism and radicalism in society. Several studies indicate that wasathiyah is a concept of teaching aimed at producing a moderate character in every aspect of community life. This research aims to uncover the concept of wasathiyah by using QS. 2:143 as the primary source and revealing its meaning through the ma'na cum maghza approach. This study is a library research using a qualitative method based on a deconstructive paradigm—the interpretation of QS. 2:143 is conducted with textual-literal analysis (grammar study) combined with contextual analysis (micro and macro historical study). Both reviews were conducted to understand the substance of the phenomenal historical meaning and the significant dynamics of the implementation of QS. 2:143. The sources of literature used are books on understanding, grammar, and history as data sources in this research. The results of the study show that based on QS. 2:143, wasatiyah is a hallmark of Islam, which does not teach ideologies and doctrines of extremism. Islam also provides certain limitations on radical and liberal thoughts that allow reason to work outside the control of the heart in practice. Thus, in the contemporary context, the discourse of wasathiyah represents Islam's position as a religion that has many methodologies and pays attention to the aspect of balance within it, not only in social behavior but also in worship practices, beliefs, and mu'amalah.